A Methodological Proposal for the Study of Semantic Functions across Languages - Labrador De La Cruz, Belén (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2004)
AbstractAfter a brief revision of the major currents of thought and grammatical models in the history of CS (Contrastive Studies), a method of analysis suitable for corpus-based descriptive studies across languages is presented and discussed in this paper. As an alternative to translation corpora, the use of comparable corpora is advocated and put into practice in a large-scale research on a particular semantic function, quantification, and its expression in two languages, English and Spanish. The different phases of the process are explained and a summary of achievements is provided. The ultimate purpose of the paper is to contribute to the strengthening of the discipline by offering new results about one pair of languages and by suggesting a methodology that can be broadly applied to different semantic fields and pairs of languages.